Stingless bee-keeping (Hymenoptera: Apidae: Meliponini) and Its Potency for Other Related-Ventures in West Sumatra. Issue 1 (June 2021) - Herwina, H; Salmah, S; Janra, M N; Mairawita,; Nurdin, J; Jasmi,; Yaherwandi,; Rusdimansyah,; Sari, D A
Abstract: Stingless bees play important role in many aspects of human livelihood since people have now recognized the benefit of pollen, honey, and cerumen of stingless bees. From survey conducted across the beekeepers in West Sumatra Province, a total of 13 stingless bee species were identified from the West Sumatran beekeeping activities. The survey also aimed to assess the current condition of stingless beekeeping in this province. Heterotrigona itama was recorded as the most popular species for beekeeping, followed by Geniotrigona thoracica and Tetragonula laeviceps, while several Tetragonula members were the least favoured by the beekeepers, i.e. T. minangkabau, T. fuscobaelata and T. testaceitarsis . The number of colonies, experience in practicing beekeeping, marketing, beekeeper networking and other related aspects were also discussed in this paper.